Faculty quality in foreing language departaments at the university level in El Salvador - Durán Hernández, Sandra Carolina (Universidad de El Salvador ;, 2004)
This research has been carried out with the purpose of establishing a scientific panorama on faculty quality in six universities holding majors in English and English Teaching. Since the concept of quality has various connotations, based on the literature reviewed, certain criteria have been chosen to focus on those elements that contribute to attain quality. Among these elements, research, teaching and community service/outreach will be the ones guiding the discussion. As every aspect is developed, the readers will figure out some of the internal and external factors that influence quality, as well as polices used in the universities to maintain and achieve quality. The paper is divided into three chapters. In the first chapter, the reader is introduced with plenty of literature providing the basis to support the inquiry. The second chapter holds a brief description on the procedural aspects for designing the instruments, choosing the research target and collecting data. The third part of the paper encloses the nucleus of the investigation. This chapter presents a detailed analysis on the criteria previously mentioned. The analysis is supported by both, the information provided in the literature review and the data provided by the sample studied. Finally, this third chapter describes the findings about the foreign language faculty quality in the six universities being targeted. Through this research project, the audience finds a wide view of the situation in higher education, specifically that of the English Language Faculty and Departments. Faculty strengths and weaknesses are brought to light as to provide elements that contribute to improve or assure quality